A Coin Trapped in Meckel’s Diverticulum - Levent CANKORKMAZ (Bezmiâlem Science, 2021)

(untitled)
Foreign body ingestion is a common problem among children. Most foreign bodies that have passed the esophagus will pass uneventfully through the intestinal tract. Foreign bodies that remain blocked in the narrower segments of the gastrointestinal tract require intervention. We herein report the case of a child who presented with a coin trapped in Meckel’s diverticulum (MD). A 2-year-old boy was brought to our hospital 3 months after ingestion of coin. Physical examination showed no abdominal tenderness. Laboratory was normal. The foreign body appeared to be a coin located in the middle lower quadrant in the abdominal X-ray. Exploratory laparotomy was performed, and Meckel's diverticulum was discovered. The coin was detected in Meckel?’s diverticulum and it wedge resection were performed. After the operation, the patient had an uneventful recovery and started enteral feeding within 5 days. Early treatment of ingested foreign bodies in the gastrointestinal system is important in terms of preventing possible complications. The determination of the exact location of the coin, decision for intervention, and management may be difficult in cases with prolonged lodgment. The diagnosis of MD should be considered when there is a prolonged lodgment of a foreign body in the lower quadrant.